Fatherless Students' Strategies in Maintaining Academic Achievement at MA Nurul Ummah Sampit - Putri Ayu Lestari; Sudarmono; Apuanor (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
psychological and academic problems among students. The loss of a father's role in a child's life has the potential to impact emotional development, learning motivation, and academic achievement. However, not all students experience this condition; research shows that being fatherless is associated with a decline in academic achievement. Some students are still able to maintain and even achieve good academic performance through various efforts and strategies. Therefore, this study aims to analyze the strategies used by students fatherless in maintaining academic achievements at MA Nurul Ummah Sampit. This research employed a qualitative approach with a case study design. The subjects were two eleventh-grade students experiencing fatherlessness, while one homeroom teacher served as a supporting informant. Data were collected through in-depth interviews, observation, and documentation. Furthermore, the data were analyzed using descriptive qualitative analysis techniques through the stages of data collection, data reduction, data presentation, and conclusion drawing. The results of the study indicate that fatherless students employ several strategies to maintain academic achievement, including managing their study time independently, actively participating in learning activities, utilizing various additional learning resources, maintaining learning motivation, and being able to deal adaptively with academic pressure. In addition to these internal factors, students' success in maintaining academic achievement is also supported by external factors such as support from their mothers, teachers, peers, and a conducive school environment. The findings of this study indicate that the condition of being fatherless is not always an obstacle to achieving academic achievement if students have good academic resilience and receive adequate social support from their surroundings.